Islamic Religious Education Curriculum Innovation: Fethullah Gülen's Perspective - Muhamad Restu Fauzi; Tasman Hamami; Hyung-Jun Kim (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This study aims to (1) Formulate what is the ideal orientation of Islamic religious education according to Fethullah Gülen and (2) Formulate Islamic religious education curriculum innovations from the Gülen perspective in the realm of objectives, materials, media, methods, and evaluations. Design/methods/approach – This study was a literature research. The source of data in this study was the works of Gülen. The data collection method used the documentation method. The data analysis method used the content analysis method through several stages of reading the entire data, encoding, code sorting, finding relationships between categories, and formulating the meaning. Findings – The findings were (1) The ideal Islamic religious education, according to Gülen, should include educating and shaping individual character, and (2) The purpose of the Islamic religious education curriculum, according to Gülen, is to create Islamic religious education that is relevant to the times, high in quality, and strengthening the identity of Muslims; Learning materials comprise content expansion that integrates classical religious texts with contemporary science; Learning media must make Islamic religious education more interesting and challenging for students so that they are more interested in learning Islam; The learning method involves students actively and collaboratively in the learning process; and Curriculum evaluation includes aspects of the quality of learning materials, learning methods, and learning outcomes. Research implications/limitations – The research has implications for developing Islamic religious education curricula that focus on a more inclusive, moderate, and relevant approach to the needs of the times. It can affect the way schools educate, encourage intercultural dialogue, and promote universal values such as tolerance and peace. Originality/value – This study has explored Gülen's perspective on the innovation of the Islamic religious education curriculum. By examining its perspective, this research provides new insights and presents a unique perspective on curriculum development.